Uncorrected visual acuity, postoperative astigmatism, and dry eye symptoms are major determinants of patient satisfaction: a comparative, real-life study of femtosecond laser in situ keratomileusis and small incision lenticule extraction for myopia - Pietilä, Juhani (Clin Ophthalmol, 2018)
PURPOSE: To compare factors affecting patient satisfaction after femtosecond laser in situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) for myopia in the real-life situation study. METHODS: The SMILE group included 100 eyes (51 patients) and the FS-LASIK group 200 eyes (102 patients). In addition to clinical examination, dry eye symptoms and patient satisfaction with far and near vision were reported and graded on the visual analog scale preoperatively and one month after the operation. Case–control pairs were selected for the SMILE patients from FS-LASIK-treated patients to ensure the homogeneity in spherical equivalent refraction, preoperative dry eye, and visual satisfaction. RESULTS: Eighty percent of SMILE eyes and 83% of FS-LASIK eyes achieved an uncorrected distance visual acuity of 20/20 or better. Predictability (±0.5 D of mean target spherical equivalent refraction) was 91% in SMILE and 93.5% in FS-LASIK. No eyes lost two or more Snellen lines of corrected distance visual acuity. Based on case–control pairs, dry eye symptoms remained the same after one month in the FS-LASIK-treated eyes (P=0.87) but decreased in the SMILE-treated eyes (P=0.01) compared with the preoperative situation. Patient satisfaction with far vision improved significantly in both groups (P<0.001), but satisfaction with near vision improved significantly only in FS-LASIK (P<0.001) and not in SMILE (P=0.58). There was more postoperative astigmatism in SMILE in comparison with FS-LASIK (P=0.002). CONCLUSIONS: In a real-life situation, patients with preoperative dry eye experience were often directed to the SMILE operation, which resulted in beneficial decrease in their dry eye symptoms. Patient satisfaction with far vision decreased with increasing dry eye symptoms and postoperative astigmatism in both SMILE- and FS-LASIK-treated emmetropic patients. Safety, efficacy, and predictability were comparable in both treatments.